Radio transmission characteristics in tunnel environments. (3rd April 2017) - Bedford, Michael D.; Kennedy, Gareth A.; Foster, Patrick J.
Abstract: Radio communication is becoming more widely used in underground mining, although it is still a challenge to achieve good quality and reliable coverage. This research provides information to assist mining professionals in designing voice or data communication systems that operate underground by transmitting along mine tunnels. This has been achieved by presenting a simplified model for predicting the propagation of microwave signals and supplementing this with the results of an extensive experimental study aimed at understanding how the performance predicted by the model differs from real-world performance. The results validate the model under ideal conditions but additional signal attenuation is shown to occur when operating close to a wall, behind a partial obstruction or in a side tunnel. Experimental results indicate the typical magnitude of such additional attenuation. Also, long- and short-range fluctuations to the predicted average is demonstrated and their typical magnitude shown. A system planning approach is outlined.